Python Data Science Essentials - Boschetti, Alberto; Massaron, Luca (Packt Publishing, 2015)
"Python Data Science Essentials" is your complete guide to mastering the applications of Python in the field of data science. This book will take you through setting up your environment, data preprocessing, machine learning, and visualization, providing hands-on examples and clear explanations.What this Book will help me doSet up a Python environment for scientific computing on various OS platforms.Preprocess data for analysis through fixing, transforming, and exploration.Apply and tune machine learning algorithms to solve data science problems.Analyze and interpret data connections using graph-based methods.Create compelling visualizations to effectively present analysis results.Author(s)Alberto Boschetti is a recognized expert in data science and Python programming, with years of experience teaching and practicing in the field. He specializes in making complex technical topics accessible through practical examples and real-world applications, ensuring readers can readily apply what they learn.Who is it for?This book is designed for aspiring data scientists who have basic Python skills and want to advance to real-world data science tasks. Data analysts familiar with languages like R or MATLAB will benefit from the focus on Python tools. It's ideal for learners aiming to efficiently solve real-world problems using data science.